2012
DOI: 10.4172/2157-7145.s1-005
|View full text |Cite
|
Sign up to set email alerts
|

Variability of Finger Ridge Density among Thai Adolescents

Abstract: Finger ridge density (RD) is the number of finger ridges that touch the diagonal line drawn between a square of 25 mm 2 which is placed on the core of the fingerprint image. It has been useful as a sex determination aid in forensic practice as its values are significantly higher in females than males. The present study was aimed at investigating the RD of Thai adolescents aged between 10 and 12 years old. Subjects were 130 schoolboys and 130 schoolgirls were randomly selected and signed informed consent forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 14 publications
1
4
0
1
Order By: Relevance
“…The frequency distribution highlights lower ridge density in the proximal area and, thus, thicker ridges in the area. It is noteworthy that the findings on the Indian population in the present study and findings from a previous study on the Thai populations show higher range of ridge density values than the African Americans and the Caucasians of America . The present findings show that the core values were highest for both the sexes and the proximal area exhibited the lowest ridge density.…”
Section: Discussionsupporting
confidence: 57%
“…The frequency distribution highlights lower ridge density in the proximal area and, thus, thicker ridges in the area. It is noteworthy that the findings on the Indian population in the present study and findings from a previous study on the Thai populations show higher range of ridge density values than the African Americans and the Caucasians of America . The present findings show that the core values were highest for both the sexes and the proximal area exhibited the lowest ridge density.…”
Section: Discussionsupporting
confidence: 57%
“…A significant correlation was found between primary fingerprint patterns and ABO–Rh blood groups. These findings are similar to earlier studies (Sandhu et al ., 2017; Manikandan et al ., 2019; Patil et al ., 2019; Fayrouz et al ., 2012; Nanakorn et al ., 2013; Ahmad and Karmakar, 2014). In contrast, a few studies did not support such associations (Chaudhary et al ., 2017; Kc et al ., 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have demonstrated an ethnic variation in the proportion of fingerprint pattern types among various populations (Lĭ et al. , 2006; Zhang et al ., 2010; Nanakorn, Kutanan, & Chusilp, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Во многих исследованиях сообщается о различиях между мужчинами и женщинами в плотности гребней, выявленных путём определения их плотности, тем не менее большинство этих исследований были связаны с плотностью гребней отпечатков пальцев, а не ладоней [9][10][11][12][13][14][15]. Что касается отпечатков ладоней, предыдущие исследования доказали их полезность в определении пола [1,14,16,17].…”
Section: обоснованиеunclassified